Identification of Bordetella holmesii among the patients hospitalized with suspicion of pertussis and pertussis-like illnesses - N. T. Gadua (Žurnal Infektologii, 2019)
Purpose. To reveal and estimate prevalence of B. holmesii among the patients hospitalized with suspicion pertussis and pertussis-like illnesses.Materials and methods. 424 clinical samples received from patients with of pertussis and pertussis-like illnesses in GBUZ IKB № 1 DZM in 2017–2018 are investigated. Identification of fragments of a genome of Bordetella was carried out in PCR-RT with “Amplisens® Bordetella multi-FL”. For identification of fragments of a genome of B. holmesii used PCR-RT with primers of IS481, IS1001 and hIS1001.Results. The research included 424 patients, from them 56,1% of children aged till 1 year, 41,3% of children – are more senior than 1 year and 2,6% of adults. When using test system 60,4% of the samples containing DNA of B. pertussis are revealed; 1,9% of samples – DNA of B. parapertussis; in 34,9% of samples it is received negative and in 2,8% – doubtful results. The research of 424 samples in PCR-RT by means of IS481, IS1001 and hIS1001 primers showed that 61,1% of samples contained DNA of B. pertussis; 0,7% of samples – DNA of B. parapertussis and 3,8% of samples – DNA of B. holmesii. In 143 samples the result was negative. From 16 DNA of B. holmesii – positive samples, 9 samples were negative in test system earlier, in 2 samples – the doubtful result, 1 sample was earlier identified as DNA of B. parapertussis and in 4 samples DNA of B. pertussis and B. holmesii are found.Conclusion. The research demonstrates circulation of B. holmesii in the territory of Russia that is confirmed by identification of positive samples in 3,8% of cases among the sick children and adults hospitalized in a hospital with suspicion of pertussis and pertussis-like illnesses. For increase in efficiency of laboratory confirmation of the clinical diagnosis of pertussis and pertussis-like illnesses the genodiagnostic of a pertussis is recommended to improve taking into account identification DNA of B. holmesii.